Efficacy of Reciproc® and Profile® Instruments in the Removal of Gutta-Percha from Straight and Curved Root Canals ex Vivo - Karem Marfisi; Montserrat Mercadé; Gianluca Plotino; Tatiana Clavel; Fernando Duran-Sindreu; Miguel Roig (Stilus Optimus, 2015)
Objectives: To compare the efficacy of Reciproc® (VDW GmbH) and ProFile® (Dentsply Maillefer) instruments at removing gutta-percha from straight and curved root canals ex vivo filled using the cold lateral condensation and GuttaMaster® (VDW GmbH) techniques. Material and Methods: Forty mesial roots of mandibular molars with two curved canals and 80 single-rooted teeth with straight root canals, a total of 160 root canals, were randomly assigned to eight groups (canals per group = 20) according to filling technique, retreatment instrument and root canal curvature as follows: Group I, cold lateral condensation/ProFile®/straight; Group II, cold lateral condensation/ProFile®/curved; Group III, cold lateral condensation/Reciproc®/straight; Group IV, cold lateral condensation/Reciproc®/curved; Group V, GuttaMaster®/ProFile®/straight; Group VI, GuttaMaster®/ProFile®/curved; Group VII, GuttaMaster®/Reciproc®/straight; and Group VIII, GuttaMaster®/Reciproc®/curved. The following data were recorded: procedural errors, retreatment duration and canal wall cleanliness. Means and standard deviations were calculated and analysed using the Kruskal-Wallis test, one-way analysis of variance and Tukey's test (P < 0.05). Results: Reciproc® instruments were significantly faster than ProFile® instruments at removing GuttaMaster® from both straight (P = 0.0001) and curved (P = 0.0003) root canals. Reciproc® were statistically more effective than ProFile® instruments in removing GuttaMaster® from straight root canals (P = 0.021). Regardless of filling technique or retreatment instrument, gutta-percha was removed more rapidly from curved than from straight root canals (P = 0.0001). Conclusions: Neither system completely removed filling material from the root canals. Compared with ProFile® instruments, Reciproc® instruments removed GuttaMaster® filling material from straight and curved root canals more rapidly.